2014
DOI: 10.1145/2581377
|View full text |Cite
|
Sign up to set email alerts
|

Solving the Search for Source Code

Abstract: Programmers frequently search for source code to reuse using keyword searches. The search effectiveness in facilitating reuse, however, depends on the programmer's ability to specify a query that captures how the desired code may have been implemented. Further, the results often include many irrelevant matches that must be filtered manually. More semantic search approaches could address these limitations, yet existing approaches are either not flexible enough to find approximate matches or require the programm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 70 publications
0
70
0
Order By: Relevance
“…Surveys asking programmers why they search for code on the Internet have been conducted by Sim et al [107], Sadowski et al [97], Stolee et al [116], and Hucka and Graham [53]. In Sim et al's survey, all 69 participants reported that they searched on the Internet either for code to use as a reference or for code that they can use as-is.…”
Section: Surveysmentioning
confidence: 99%
See 3 more Smart Citations
“…Surveys asking programmers why they search for code on the Internet have been conducted by Sim et al [107], Sadowski et al [97], Stolee et al [116], and Hucka and Graham [53]. In Sim et al's survey, all 69 participants reported that they searched on the Internet either for code to use as a reference or for code that they can use as-is.…”
Section: Surveysmentioning
confidence: 99%
“…To address this, our approach was simply to do a literature search to determine how many results people, in general, look at. We discovered that, in general, they do not look past the top ten results from a query [21], [56], [117]. As such, we decided to set , the size of , to be 10.…”
Section: Size Of Smentioning
confidence: 99%
See 2 more Smart Citations
“…Stolee et al [25] examined the use of semantic models of source code as an indexing strategy to help find a block of code that will pass a set of test cases -one form of goal-based search. Such semantic searches have additionally been used in web service composition [26], [27].…”
Section: Related Workmentioning
confidence: 99%